(untitled) (The Chittagong University Journal of Science, 2021)
Onset of menstruation is the biological and physical indicator, which is one of the important components of female reproductive characteristics. Considering its importance in the context of reproductive health and fertility, the aim of this study is to determine the mean age at menarche and also to investigate the patterns and differentials of such an important vital event of the randomly selected girls aged 9-15 years from the schools of Chittagong metropolitan area. The results of this study show that the overall mean menarcheal age of the selected girls is only 11.75±0.97 years with significant variations by their background characteristics. The co-efficient of variation (8.3%) indicates that there exists extreme heterogeneity in menarcheal age of the respondents. Co-efficient of skewness (β1=0.15) and excess of kurtosis (γ2=0.35) reflect that the shape characteristics of age at menarche is positively skewed and leptokurtic. The mean age at menarche is computed as relatively low (11.37 years) among the respondents residing in the metropolitan areas. The mean age at menarche is found the highest (12.01 years) among the underweight and the lowest among overweight (11.43 years) girls. The results from the life table technique show that unexpectedly 1.2% girls likely to attain menarche only within age of 9.67 years. The value of spread (s=16 months) shows extreme heterogeneity in menarcheal age. The values of trimean of onset of menstruation for underweight, normal and overweight girls are found 11.83, 11.58 and 11.41 years respectively. The Chittagong Univ. J. Sci. 40(1) : 178-199, 2019